2016
DOI: 10.3390/agronomy6010005
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Trapping of Soil Contaminants by Root Border Cells: New Insights into Plant Defense

Abstract: Soil and water pollution by metals and other toxic chemicals is difficult to measure and control, and, as such, presents an ongoing global threat to sustainable agriculture and human health. Efforts to remove contaminants by plant-mediated pathways, or "phytoremediation", though widely studied, have failed to yield consistent, predictable removal of biological and chemical contaminants. Emerging research has revealed that one major limitation to using plants to clean up the environment is that plants are progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 71 publications
(55 reference statements)
0
35
0
2
Order By: Relevance
“…Oberkochen, Germany) to ensure proper root tip and border cell formation. Root border cells, which dissociate from the root tip upon contact with water, were separated and collected from the root tip by micropipetting [16][17][18][19][20][21][22][23][24]. Border cell numbers were counted from 10 µL aliquot samples of the border cell-sdH 2 O suspension using an Olympus BX60F5 compound microscope.…”
Section: Root Border Cell Numbermentioning
confidence: 99%
“…Oberkochen, Germany) to ensure proper root tip and border cell formation. Root border cells, which dissociate from the root tip upon contact with water, were separated and collected from the root tip by micropipetting [16][17][18][19][20][21][22][23][24]. Border cell numbers were counted from 10 µL aliquot samples of the border cell-sdH 2 O suspension using an Olympus BX60F5 compound microscope.…”
Section: Root Border Cell Numbermentioning
confidence: 99%
“…Furthermore, exDNA plays a critical role in the structural integrity of the complex extracellular trap structures surrounding border cells. Future studies to define the process and how it varies in response to pathogens, toxins, metals (Hawes et al, 2016b), and other dangers are needed. Rather than providing a convenient system to observe how infection occurs at the cellular level (e.g., Hawes and Pueppke, 1986, 1987), border cells instead may provide a tool to define how infection and injury are prevented.…”
Section: Discussionmentioning
confidence: 99%
“…Most plant species are programmed to synthesize and deliver populations of metabolically active cells from the root tip into the soil environment (Knudson, 1919; Hawes and Pueppke, 1986; Hawes et al, 1998; Hawes et al, 2016a, b). Gene expression patterns in these root “border” cells are distinct from progenitor cells in the root cap, and the cells actively export a complex matrix that includes >100 extracellular proteins (Brigham et al, 1995, 1998; Knox et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA staining was visible surrounding the border cells and surface of the peripheral root cap, with no staining inside the border cells. Interestingly, recent findings revealed that soil contaminants can be entrapped within extracellular DNA released by root border cells [164]. The authors proposed that a better understanding of border cell ETs would help develop a non-destructive approach to neutralise environmental threats [164].…”
Section: Extracellular Traps In Plantsmentioning
confidence: 99%